Pengaruh Ukuran Dewan Komisaris, Komisaris Independen dan Leverage Terhadap Pengungkapan Enterprise Risk Management Pada Perusahaan Perbankan Yang Terdaftar Di Bursa Efek Indonesia Pada Tahun 2016-2020 - Hendry Setya Pambudi; Nurma Gupita Dewi (Jurnal Ekonomika dan Bisnis, 2023)
The purpose of this paper is to know about the influence of board size, independent commissioners, and leverage on enterprise risk management (ERM) disclosures. By applying the purposive sampling method, in which a sample of 16 banks listed on the Indonesia Stock Exchange from 2016 to 2020 uses documentation data. SPSS 26 is used as data analysis software for multiple linear regression analysis. According to the findings of this study, leverage has a positive but insignificant effect on ERM disclosure, board size has a significant positive effect on ERM disclosure, and independent commissioners have a negatively significant effect on ERM disclosure.